Demand-driven sales and operations planning: a framework proposal - Bozutti, Daniel Fernando (2020)
In a period of great technological advances and social and economic changes, the competitive environment is challenging for companies, which requires them to take actions towards flexibility, collaboration, integration, agility, velocity, traceability and cost-effective operations and supply chains. Both scholars and practitioners are employing the term Demand-Driven (DD) to characterize companies able to respond to these dynamic characteristics. Additionally, a critical process which has the aim of matching the supply with the demand is the Sales and Operations Planning (S&OP) and this process requires an updated understanding and the necessity of changes considering the new competitiveness environment, which also requires customer centricity and being driven by demand. Based on this, this thesis had the objective of proposing a framework for the Demand-Driven Sales and Operations Planning (DDS&OP). To achieve this objective two systematics literature (SLR) reviews were conducted, one for DD phenomenon and other for S&OP process. Based on both SLRs, the framework for the DDS&OP was proposed and it was modelled in BPMN. The framework considered three perspectives (strategic, tactical and operational) and the governance of the process. The framework was validated with 17 experts from different areas (scholars and practitioners from different industries) through the Fuzzy-Delphi Method. The main result of the thesis was a framework for the DDS&OP proposed upon a robust theoretical method and validated by experts. Other results were: a common definition for the DD phenomenon presented, a structuring and unifying conceptual framework for the DD phenomenon, the necessity of expansion of both vertical and horizontal consistencies for the S&OP and a list of 20 approaches that should be considered in the S&OP process for the new competitiveness environment.